Rethinking the Art of Tattoo: A Perspective of Indonesian Women Tattoo Community - Lambok Hermanto Sihombing (Lingua Cultura, 2021)
The research analyzed why women decided to get tattoos on their bodies and how Indonesian women interpreted tattoos. The tattoo was a kind of art and a symbol since centuries ago. In Indonesia, having a tattoo was no longer considered taboo as it used to be seen as something that deviated from the norm in Indonesia, especially if it was possessed by women. The tattoo was also identical with crime and thuggery, in which people who had tattoos would be respected or feared by people. However, in recent years, there has been a phenomenon in the raising of female tattoo communities where tattooed women gathered and supported each other. The research used the tattoo concept by Thompson and Feminist theory by Kristeva to analyze it. The research applied a qualitative method in which the dataset were taken from interview with three women of the Perempuan Tattoo Indonesia (PTI) community. The result of the interview is various. It shows that tattoo in Indonesian women’s perspective is not seen as only a trend, fashion, or art. However, it shows self-expression and freedom to fight women’s rights and gender quality.